Taṭwīr Māddah Ta‘Līm An-Naḥw Bi Ṣūrat As-Su’āl Wa Al-Jawāb Li Tarqiyat Fahm An-Naḥw Li Ṭullāb Maskan Aṣ-Ṣaff Ath-Thāmin Fī Al-Madrasah Al-Mutawassiṭah Mu‘Allimīn Nahḍat Al-Waṭan Ad-Dīniyyah Al-Islāmiyyah: تطوير مادة تعليم النحو بصورة السؤال و الجواب لترقية فهم النحو لطلاب مسكن الصف الثامن فى المدرسة المتوسطة معلمين نهضة الوطن الدينية الإسلامية - Ruwaida Hudatullah; Muhammad Jum’ah Fathi Ramdhan (The Center for Language Development, Mataram State Islamic University., 2025)
Understanding Nahwu in Islamic boarding schools is very important because it serves as the foundation for comprehending Arabic texts. However, many students still find it difficult to understand Nahwu material delivered by their teachers. This difficulty is caused by several factors, including differences in students’ educational backgrounds—some come from elementary schools (SD) and Islamic elementary schools (MI). In addition, their learning environment also influences their comprehension, and the textbooks used in learning are often too advanced for the MTs level. Therefore, it is necessary to develop teaching materials that are easy to understand and appropriate to the students’ abilities. This study aims to: (1) describe the development of the Nahwu Question and Answer teaching material in improving the Nahwu understanding of grade VIII students at MTs Mu’allimin NWDI Pancor, (2) identify students’ responses toward the teaching material, and (3) determine the effectiveness of the material. The research employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), while data collection techniques included questionnaires, tests, interviews, observations, and documentation. The results of this study are as follows: (1) The validation level of the Nahwu Question and Answer teaching material was categorized as “very valid” based on the validators’ assessments. The media expert gave a score of 100% (very valid), while the material expert gave 82% (also very valid). Based on these evaluations, the product was declared feasible to be used and tested in the learning process. (2) A total of 30 students were given questionnaires to assess the use of the Nahwu Question and Answer book. The results showed that 94.67% of respondents rated it as “excellent,” indicating that the use of this teaching material is highly feasible. (3) Learning outcomes also improved, with the average pre-test score increasing from 78.43% to 95.86% in the post-test, and a significance value (Sig. 2-tailed) of 0.000. Since the significance value is smaller than the established significance level(α = 0.05), it can be concluded that there is a significant difference between the pre-test and post-test results. This proves that the use of the Nahwu Question and Answer teaching material in the learning process is highly effective in improving students understanding of Nahwu.